Unverfügbares Verinnerlichen. Figuren der Einverleibung zwischen Eucharistie und Anthropophagie - Al-Taie, Yvonne; Famula, Marta (Amsterdamer Beiträge zur neueren Germanistik)

Das große Welttheater. Eine überzeitliche Chiffre des Barock /Pedro Calderón de la Barca – El gran teatro del mundo - Schreckenberg, Stefan; Schmitz, Sabine (Peter Paul Rubens und der Barock im Norden)

Lernwerkstätten - Kottmann, Brigitte (Handbuch Ganztagsbildung)

Clinching in in-situ CT—A numerical study on suitable tool materials - Köhler, Daniel; Kupfer, Robert; Gude, Maik (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Controversial Histories – Current Views on the Crusades. Engaging the Crusades, Volume Three.

Modern WLAN for V2X Applications: Exploiting Beamforming for Platooning - Hardes, Tobias; Klingler, Florian; Sommer, Christoph (12th IEEE Vehicular Networking Conference (VNC 2020))
A key challenge in the domain of Inter-Vehicle Communication (IVC) is to make the best use of limited channel capacity to achieve a continuous exchange of information. In this work, we propose the use of directional radio transmission and reception (known from modern WLAN standards, but following the IEEE 802.11p specifications) to lower the channel utilization. In this work, we use platooning as an example application, since this application offers a well-defined communication topology. Using extensive simulations, we show that directional communication can substantially lower the channel busy ratio to less then half for platoon vehicles and down to less than 1% for non-platoon vehicles. If care is not taken, however, it can drastically increase the probability for packet collisions.

Using Full Duplex Relaying to Reduce Physical Layer Latency in Platooning - Amjad, Muhammad Sohaib; Hardes, Tobias; Schettler, Max; Sommer, Christoph; Dressler, Falko (2019 IEEE Vehicular Networking Conference (VNC))

Towards Heterogeneous Communication Strategies for Urban Platooning at Intersections - Hardes, Tobias; Sommer, Christoph (2019 IEEE Vehicular Networking Conference (VNC))
Platooning promises to solve worldwide traffic problems by using wireless communication for tight control of convoys of vehicles to reduce their inter-vehicle gaps. To date, however, most research on platooning has focused on freeway scenarios. In this paper, we provide a realistic exploration of platooning in urban environments: We consider traffic lights and buildings, realistic vehicle dynamics, platooning controllers, and network communication. We highlight the challenges that urban platooning faces because of the particularities of the Radio Frequency (RF) channel, specifically near the centers of intersections. We demonstrate that using Visible Light Communication (VLC) as an alternative can alleviate some problems, but causes others. Using extensive simulations, we show how a situation-aware combination of VLC and RF communication can be used as a solution: It reduces the overall amount of lost information by approx. 85% compared to traditional approaches.

Entwicklung eines Fachpraktikums im Techniklehramt - Ermel, Dorothee Leonie; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. GDCP-Jahrestagung, 2019 in Wien)

Jonas Leineweber/ Peter Karl Becker/ Dagmar Troska/ Philipp Rustemeier: Das Schützenwesen in Westfalen als Immaterielles Kulturerbe